Network Pharmacology-Based Strategy for the Investigation of the Anti-Osteoporosis Effects and Underlying Mechanism of Zhuangguguanjie Formulation - Gong, Wang; Chen, Xingren; Shi, Tianshu; Shao, Xiaoyan; An, Xueying; Qin, Jianghui; Chen, Xiang; Jiang, Qing; Guo, Baosheng (Frontiers in Pharmacology, 2021)
As the society ageing, the increasing prevalence of osteoporosis has generated huge social and economic impact, while the drug therapy for osteoporosis is limited due to multiple targets involved in this disease. Zhuangguguanjie formulation (ZG) is extensively used in the clinical treatment for bone and joint diseases, but the underlying mechanism has not been fully described. This study aimed to examine the therapeutic effect and potential mechanism of ZG on postmenopausal osteoporosis. The ovariectomized (OVX) mice were treated with normal saline or ZG for four weeks after ovariectomy for following a series of analysis. The bone mass density (BMD) and trabecular parameters of femur were examined by micro-CT. The bone remodeling was evaluated by bone histomorphometry analysis and ELISA assay of bone turnover biomarkers in serum. The possible drug-disease common targets were analyzed by network pharmacology. To predict the potential biological processes and related pathways, GO/KEGG enrichment analysis were performed. The effects of ZG on the differentiation phenotype of osteoclasts and osteoblasts and the predicted pathway were verified in vitro. The results showed that ZG significantly improved the bone mass and micro trabecular architecture in OVX mice compared with untreated OVX mice. ZG could promote bone formation and inhibit bone resorption to ameliorate ovariectomy-induced osteoporosis as evidenced by increased number of osteoblast (N.Ob/Tb.Pm) and decreased number of osteoclast (N.Oc/Tb.Pm) in treated group comparing untreated OVX mice. After identifying potential drug-disease common targets by network pharmacology, GO enrichment analysis predicted that ZG might affect various biological processes including osteoblastic differentiation and osteoclast differentiation. KEGG enrichment analysis suggested that PI3K/Akt and mTOR signaling pathway could be the possible pathways. Further, the experiments in vitro validated our findings. ZG significantly down-regulated the expression of osteoclast differentiation markers, reduced osteoclastic resorption and inhibited the phosphorylation of PI3K/Akt, while ZG obviously up-regulated the expression of osteogenic biomarkers, promoted the formation of calcium nodules and hampered the phosphorylation of 70S6K1/mTOR, which can be reversed by corresponding pathway activator. Thus, our study suggested that ZG could inhibit PI3K/Akt signaling pathway to reduce osteoclastic bone resorption as well as hamper mTORC1/S6K1 signaling pathway to promote osteoblastic bone formation.